Study of the effects of cosmetic preparations containing resveratrol on facial skin ageing process (Journal of Face Aesthetics, 2021)
Introduction. Skin ageing is a natural process occurring under the influence of endogenous and exogenous factors. Due to its properties, resveratrol can be used as an active ingredient of anti‑ageing cosmetics intended for skin protection against the photoaging process.Aim. The aim of this research paper was to assess the influence of a series of treatments and home skin care based on preparations containing resveratrol and other natural ingredients, on the facial skin ageing processes delay.Material and Methods. The study included 15 women, aged 30–65, with healthy facial skin and with minor or major signs of skin ageing, such as: loss of moisture, loss of skin firmness, enlarged pores, or wrinkles. The study consisted in performing a series of 3 Resveravit C Peel 50% Back To Comfort treatments at a beauty studio, supplemented with home skin care with the use of Resveravit C anti‑ageing preparations, and skin analysis with the use of POLDERMA EXPLORE 3D instrument, before and after the treatment. Statistical analysis was performed.Results. Skin parameters analysis has shown that Resveravit C Peel 50% Back To Comfort treatment and home treatment with Resveravit C anti‑ageing improved the skin firmness, reduced the number of wrinkles, and enlarged pores, and reduced brown spots.Conclusions. Treatments and cosmetic preparations containing resveratrol can effectively reduce the signs of skin ageing.
Keywords: skin diagnostics; cutometer; coefficient of elasticity – parameter R8/R0